Worker's compensation usage and return to work outcomes for Ontario public safety personnel with mental stress injury claims: 2017–2021 - Edgelow, Megan; Brar, Santyna; Fecica, Agnieszka (Frontiers in Organizational Psychology, 2023)
This study explored approved worker's compensation claims made by public safety personnel (PSP) with work-related psychological injuries to the Workplace Safety and Insurance Board (WSIB) of Ontario's Mental Stress Injury Program (MSIP) between 2017 and 2021. This worker's compensation program provides access to health care coverage, loss of earnings benefits, and return to work support services for psychologically injured workers. In 2016, the Government of Ontario amended legislation to presume that, for this population, posttraumatic stress disorder (PTSD) is work-related, potentially expanding access to the program. The aim of this study was to understand the volume and types of claims, return to work rates, and differences between PSP career categories in the first 5 years after the legislative change. Using a quantitative descriptive approach, statistical analysis revealed that claims increased over the 5-year period, with significantly more claims made in 2021 (n = 1,420) compared to 2017 (n = 1,050). Of the 6,674 approved claims, 33.5% were made by police, 28.4% by paramedics, 21.6% by correctional workers, 9.4% by firefighters, and 7.1% by communicators. Analysis of claim type revealed that police, firefighters, and communicators made more cumulative incident claims, while paramedics made more single incident claims. Differences were also observed in return to work rates, with fewer police officers, firefighters, and communicators assigned to a return to work program, and more paramedics successfully completing a return to work program. This study sheds light on differences among PSP in their WSIB Ontario MSIP claims and underscores the importance of continued research to develop a more robust understanding of these differences, to inform policy development for both employers and worker's compensation organizations.